(untitled) (SCIENCE TIME JOURNAL, 2023)
In this article, in the poetry of Alisher Navoi, the psychological state of the lyrical hero in the state of death and the artistic interpretation of the processes before the state of death were studied, and the poet’s ghazals in the book "Khazayin ul-Maoni" were analyzed.